Does The Covid-19 Pandemic Affect Personal Financial Decisions In The Post-Pandemic Era? - Najmi, Nurun (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to describe and analyze changes in personal financial decisions, including consumption, saving, investment, and charitable giving, during the transition from the COVID-19 pandemic to the post-pandemic period in Indonesia. The research focuses on how perceived vulnerability shaped by personality traits, pandemic-related perceptions, social media usage, religiosity, and financial conditions influences these financial behaviors. Data were collected through an online survey involving 377 Indonesian respondents aged 17 years and above. The analysis employs descriptive statistics and non-parametric tests specifically Mann-Whitney, Kruskal-Wallis, and Wilcoxon tests to identify significant differences in financial behaviors across demographic and psychological groups. The results reveal a substantial behavioral adjustment, with individuals exhibiting higher saving tendencies, reduced non-essential consumption, and more conservative investment preferences in the post-pandemic era. Despite these shifts, spending on charitable giving remains relatively stable, indicating that prosocial financial behavior is less sensitive to external shocks compared to personal consumption or saving behavior. Furthermore, the study finds that perceptions of vulnerability and financial insecurity are widespread across demographic categories, suggesting that vulnerability is a shared psychological experience rather than one confined to specific income or age groups. These findings provide valuable insights for policymakers and financial educators in developing targeted strategies to enhance financial resilience and behavioral adaptability in the post-pandemic economy.